Gender Representation in Learning Materials International Perspectives - Mustapha, Abolaji S., 1962-, editor; Mills, Sara, 1954-, editor (New York ; London : Routledge, Taylor & Francis Group, 2015)
Includes bibliographical references (pages 219-246) and index